Preparation of graphene/nile blue nanocomposite: Application for oxygen reduction reaction and biosensing. (10th August 2015) - Shervedani, Reza Karimi; Amini, Akbar
Highlights: New nanocomposite is synthesized by electrochemical polymerization of Nile blue and reduction of GO on GCE. The nanocomposite is characterized by SEM, UV–vis and electrochemical methods. High electrocatalytic activity was observed for O2 reduction on GNs-NB nanocomposite. GCE-GNs-NBpoly was tested successfully for immobilization of GOx and detection of glucose. Abstract: Nile blue/graphene (NB-GNs) nanocomposite was synthesized for the first time via a green and effective one-step electrochemical method, allowing to reduce graphene oxide (GO) and NB on the glassy carbon electrode (GCE) simultaneously and construct GCE-GNs-NBpoly composite. The composite was characterized by scanning electron microscopy (SEM), UV–Vis spectroscopy, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The electrochemical results obtained in the absence of any redox probe, where NB was active, allowed to trace step-by-step addition of the NB-GNs nanocomposite onto the GCE electrode surface, supporting formation of the GCE-GNs-NBpoly composite. The electrocatalytic activity of the as-prepared GCE-GNs-NBpoly towards O2 reduction was studied in neutral medium. The results revealed excellent electrocatalytic performance for two-electron reduction of oxygen, suggesting its potential application as metal-free electrocatalysts for O2 reduction reaction. Application of the GCE-GNs-NBpoly in electrochemical biosensing was demonstrated by immobilization of glucose oxidase (GOx) on the surface of GCE-GNs-NBpoly, and then, using it for sensing of glucose. The biosensor exhibited a linear response, from 0.2 to 2.0 mM glucose, with a low detection limit, 2.1 μM, and high sensitivity, 67.0 μA mM −1 cm − 2, obtained by cyclic voltammetry method. The proposed biosensor was successfully tested for determination of glucose in blood serum samples.